Evaluasi Pemanfaatan Waduk Wonorejo Sebagai Pengendali Banjir Kota Balikpapan - Ezra Hartarto Pongtuluran (Publikasi dan UKI Press UKI Toraja., 2020)
Several reservoirs have been built at several points in the area to control the floods that have been hitting Balikpapan City. However, it turns out that this alternative is still not able to reduce the occurrence of standing water in several locations, including in the Wonorejo area, so it still needs to be evaluated regarding its function as a control building or merely being a water storage pool that does not have a water release control system. In solving this problem, an analysis of the reservoir's characteristics is carried out, which is the relationship between elevation, area, and reservoir capacity, which is obtained using the 3rd order polynomial regression equation. Then, the cumulative volume of inflow volume projection in the reservoir is carried out using a linear program equation to the reservoir capacity. In knowing the output channel capacity (outflow) performance, a comparison is made to the input discharge (inflow) in the reservoir as an evaluation to find out that the outflow channel will not overflow into the surrounding area. Based on the characteristic curve, it is found that the storage capacity in the Wonorejo reservoir is 0.795 MCM or 794,900.45 m3 with the total volume entering the reservoir of 1,795,034 m3, which indicates that the current performance of the reservoir has been less effective. Whereas in the reservoir outflow capacity, it was found 57.90 m3/s, when compared to the amount of input discharge (inflow) of 33.00 m3/s, it can be said that the dimensions of the outflow channel still have sufficient capacity to accommodate flood discharge from within reservoir